Orientation effect in poly (butylene succinate) fibers - Nakayama, K. (2003)
Fibers of poly (butylene succinate) (PBS) were prepared using a single screw extruder at various take-up speeds. Changes in fiber structure, morphology and physical properties were investigated using sonic velocity measurements and X-ray diffraction. High take up speeds enhanced some of the properties of PBS fibers as a consequence of changes in molecular orientation and crystallinity. Spherulites of PBS were also obtained at 90°C.